Analisis Efisiensi Kerja Mesin Pencacah Rumput dengan Variasi Jumlah 4 dan 6 Mata Pisau menggunakan Mesin 5,5 HP - Renaldo Adhe Ardianto; Budi Harjanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This research aims to determine the effect of the number of blades on the performance of a grass chopping machine, particularly on working capacity, chopping time, and the quality of chopping results, as well as to identify the most optimal blade. The research method employed was an experimental approach with a quantitative design using two variations in the number of blades, namely 4 blades and 6 blades. The tests were conducted using a grass chopping machine powered by a 5.5 HP gasoline engine operating at 2300 RPM, with elephant grass used as the test material. Each variation was tested five times under the same conditions. The performance of the machine was evaluated based on working capacity (kg/hour), chopping time (seconds), and the quality of chopping results measured by the average length of the chopped grass (cm). The results showed that the number of blades significantly affected the machine performance. The average working capacity produced by 6 blades was 274,446 kg/hour, higher than 4 blades which produced 194,698 kg/hour. The fastest chopping time using 6 blades was 12,49 seconds, while 4 blades required 17,18 seconds. In terms of chopping quality, 6 blades produced finer results with an average length of 4,16 cm compared to 4 blades with an average length of 4,52 cm. These findings indicate that the use of 6 blades provides more optimal performance in increasing working capacity, reducing chopping time, and improving the quality of chopped grass.